Isolation and characterization of a new fungal species, Fusarium equiseti (Corda) Sacc., from Brassica juncea in Bharatpur (Journal of Oilseed Brassica, 2026)
A field survey of emerging collar root disease incidence at farmer’s fields of Indian mustard (Brassica juncea L.) was conducted in Bharatpur district of Rajasthan to confirm the casual organism of the disease. The pathogen from collected diseased samples was isolated, purified and supply to Agarkar Research Institute, Pune, India for identification. Analysis of the sequences of different fragments of the ribosomal genes demonstrated that isolated pathogen species belongs to the Nectriaceae family and is genetically different from other morphologically similar species of Fusarium. This new species is unique in having colonies on PDA at 25oC+ 2oC, fast growing, rosy pink to vanacous, reverse pell leuteus to light ochraceous. As per the micromorphology, hyphae was hyaline, smooth, pigmented and 2.75-4.77μm wide. Singlespore pure culture produced chlamydospores were intercalary, fusoid, hyaline and smooth walled. Although, macroconidia were abundantly produced, fusoid, smooth walled, hyaline, foot cell present and sickle shaped, 2-septate with 14.59- 45.48 x 2.88-4.10μm in size. Though, microconidia were fusoid, 1-septate and 2.5-2.67 x 2.67-13.7 μm in size. As per our studies, the fungus was morphologically identified as Fusarium equiseti (Corda) Sacc. (NFCCI 4564).